A BIODIVERSIDADE E ALIMENTAÇÃO HUMANA: PERSPECTIVA SUSTENTÁVEL E CULTURAL - PAULINO, Isis de Oliveira; OLIVEIRA, Isaias de; OLIVEIRA, Inessa Steffany Torres de; OLIVEIRA, Isaac Torres de (ANAIS DO ENIC, 2024)
-